The impact of applying lean manufacturing systems on reducing costs of production companies in the Kingdom of Saudi Arabia for the year of 2022 - Alsayed, Huda Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to show the role played by Lean Manufacturing, which considered one of the most important industrial systems that are concerned with reducing losses of all kinds, which leads to a reduction in production costs. The researcher, distributed questionnaire lists to a sample of food manufacturing companies in the Kingdom of Saudi Arabia to prove the validity of the hypotheses. The study concluded that, there is a statistically significant relationship at a significant level of 0.05 between all three hypotheses of the study. The on-time production system contributes to following-up and correcting errors at the lowest possible cost and eliminating all activities that burden the company with indirect and unnecessary costs. Because this system depends on multi-skilled labor.
Keywords: Lean manufacturing system; cost of production; on time production; food-manufacturing companies; storage cost